The sensory and sympathetic innervation of guinea-pig lung and trachea as studied by retrograde neuronal tracing and double-labelling immunohistochemistry - Kummer, Wolfgang; Fischer, Axel; Kurkowski, R.; Heym, Christine (Neuroscience, 1992)
The sympathetic and sensory innervation of guinea-pig trachea and lung were studied by means of retrograde neuronal tracing using fluorescent dyes, and double-labelling immunofluorescence. Sympathetic neurons supplying the lung were located in stellate ganglia and in thoracic sympathetic chain ganglia T2-T4; those supplying the trachea resided in the superior cervical and stellate ganglia. Retrogradely labelled sympathetic neurons were usually immunoreactive to tyrosine hydroxylase; the majority also contained neuropeptide Y immunoreactivity. However, a small number were non-catecholaminergic (i.e. tyrosine hydroxylase negative), but neuropeptide Y immunoreactive. Within the airways, tyrosine hydroxylase/neuropeptide Y-immunoreactive axons were found in the smooth muscle layer, around blood vessels including the pulmonary artery and vein, and to a lesser extent in the lamina propria. Periarterial axons contained in addition dynorphin immunoreactivity. Sensory neurons supplying the lung were located in jugular and nodose vagal ganglia as well as in upper thoracic dorsal root ganglia; those supplying the trachea were most frequently found bilaterally in the nodose ganglia and less frequently in the jugular ganglia. A spinal origin of tracheal sensory fibres could not be consistently demonstrated. With regard to their immunoreactivity to peptides, three types of sensory neurons projecting to the airways could be distinguished: (i) substance P/dynorphin immunoreactive; (ii) substance P immunoreactive but dynorphin negative; and (iii) negative to all peptides tested. Substance P-immunoreactive neurons innervating the airways invariably contained immunoreactivity to neurokinin A and calcitonin gene-related peptide. Retrogradely labelled neurons located in the nodose ganglia belonged almost exclusively (⩾99%) to the peptide-negative group, whereas the three neuron types each represented about one-third of retrogradely labelled neurons in jugular and dorsal root ganglia. Within the airways, axons immunoreactive to substance P/neurokinin A and substance P/calcitonin gene-related peptide were distributed within the respiratory epithelium of trachea and large bronchi, in the lamina propria and smooth muscle from the trachea down to the smallest bronchioli (highest density at the bronchial level), in the alveolar walls, around systemic and pulmonary blood vessels, and within airway ganglia. Those axons also containing dynorphin immunoreactivity were restricted to the lamina propria and smooth muscle. The origin of nerve fibres immunoreactive for vasoactive intestinal polypeptide, of which a part were also neuropeptide Y immunoreactive, could not be determined by retrograde tracing experiments. Vasoactive intestinal polypeptide-immunoreactive fibres terminating within airway ganglia may be of preganglionic parasympathetic origin, whereas others (e.g. those found in smooth muscle) may arise from intrinsic ganglia. The results provide a detailed topographical and neurochemical map of the extrinsic innervation of lower airways in the guinea-pig, and reveal an extraordinary degree of complexity: (i) each functional system (sympathetic, sensory, intrinsic) is represented by at least two neurochemically distinct types of neurons; (ii) each peptide occurs in at least two distinct combinations with others; and (iii) some peptides occur in two functionally distinct systems.
Elektronische Reproduktion der Druck-Ausgabe 19. März 2003
Gesehen am 10.11.2025